EXPLOITATION OF HETEROSIS FOR YIELD AND GRAIN ZINCENRICHMENT IN RICE (Oryza Sativa L.) - P. MADHUKAR, B. SRINIVAS, P. GONYA NAYAK; B. LAXMI PRASANNA (The Journal of Research, PJTSAU, 2026)
Exploitation of heterosis is an effective strategy for enhancing grain yield and nutritional quality in rice. The present investigation was undertaken to estimate heterosis for yield, yield-attributing traits and grain zinc (Zn) concentration using a line × tester mating design involving five CMS lines, twelve testers and sixty F hybrids. The experimental material, along with the parents and standard checks, was evaluated for twelve quantitative traits including grain yield and grain Zn content. Analysis of variance revealed highly significant differences among parents, hybrids and line × tester interactions for most of the traits, indicating the presence of substantial genetic variability and the importance of both additive and non-additive gene effects in controlling these characters. Considerable heterosis over the better parent and standard checks was recorded for grain yield and its component traits. The cross CMS 69A × IET 27984 exhibited the highest heterobeltiosis for grain yield (149.62% over the better parent), while several hybrids including CMS 11A × IET 28713, CMS 11A × IET 27984, CMS 52A × IET 27984, CMS 59A × IET 28713, CMS 64A × CR Dhan 315, CMS 69A × CR Dhan 411, CMS 69A × IET 28713, and CMS 69A × IET 27984 expressed significant positive standard heterosis for grain zinc concentration, ranging from approximately 74 to 88% over the standard check. These hybrids also exhibited desirable performance for important yield-contributing traits such as filled grains per panicle, spikelet fertility, and effective bearing tillers. The results indicate the existence of substantial exploitable heterosis for simultaneous improvement of grain yield and zinc enrichment. The identified superior hybrids represent promising genetic resources for the development of high-yielding, zinc-biofortified rice hybrids and warrant further multi-location evaluation before commercial utilization.